The Role of Influencer Marketing in Boosting Sales of Local T-Shirt and Hoodie Products in the Digital Age - Sander, Steven Alex; Jonathan, Hendra; Winarko, Chirstian Nathanael; Simamora, Malvin Gamaliel; Mulyandi, M. Rachman (PT. Riset Press International, 2026)
The rapid development of digital platforms has reshaped the fashion industry and influenced how consumers make purchasing decisions. This study examines the role of influencer marketing in increasing sales of local T-shirt and hoodie products in the digital era. Using a qualitative literature review approach, this study analyzes journals, articles, and relevant research published between 2023–2025. The results indicate that influencer credibility, content quality, and audience engagement significantly impact consumer purchase intention. Influencer marketing is proven to enhance brand awareness, build consumer trust, and strengthen brand positioning in the local fashion market. Micro and nano influencers, in particular, show high engagement performance and strong persuasive power, making them highly effective for local apparel brands with limited marketing budgets. This study concludes that the strategic selection of influencers and the creation of authentic content are essential to improving sales performance in today’s competitive digital environment.